Storage effect on the bond strength of orthodontic metal brackets bonded by three types of adhesive generations (Mustansiria Dental Journal, 2018)
The effect of food simulants on the bond strength of orthodontic metal brackets bonded to enamel with light cured composite was studied. One hundred twenty extracted human premolars were selected and randomly divided into three equal groups each with 40 teeth, representing the adhesive bonding generation (5th, 6th and 7th). Each group was subdivided in to two subgroups which represented the storage media, which are distilled water (DW) and 75% aqueous ethanol (Food simulating solution-FSS). Then the storage media group was subdivided into two subgroups with 10 teeth each, representing two storage periods (1 day and 30 days).At the end of the storage period in the immersion media the brackets were debonded by an Instron universal testing machine to measure the shear bond strength.It was found immersion in the food simulants for 30 days significantly reduces the bond strength of light cured composite brackets.